(untitled) (Journal of Kidney Cancer, 2023)
The incidence of renal cell cancer (RCC) is low in individuals aged less than 40 years; however several studies have shown this increasing trend over the years. Hereditary syndromes are associated with RCC and are more frequently observed in early-onset cases. In this study, we investigated the characteristics of the patients, aged less than 40 years, who were operated for a renal mass with the suspicion of RCC. We analyzed patients aged <40 years who underwent partial or radical nephrectomy between January 2012 and December 2022. A total of 618 patients underwent partial or radical nephrectomy and 60 (9.7%) patients were aged <40 years. A total of 62 renal masses were resected. The median age of the patients was 34 (31.75–38) years. RCC was detected in 50 (80.6%) lesions, while 12 (19.4%) lesions were benign. The most commonly observed benign tumors were oncocytoma and multicystic nephroma. Low-stage RCC (stage 1) was detected in 78% of patients. Recurrence was observed in two patients and both had von Hippel–Landau gene mutation. During follow-up, two patients were found to have lung metastasis, while another patient had bone metastasis. Three patients died during the follow-up period. Disease free survival rate was 89.58% and cancer specific survival rate was 93.88%. The incidences of kidney cancer in young adults are increasing; therefore, early discovery and the diagnosis are important. Further research is required to gain a better understanding.